Sunflowers, hidden disabilities and power inequities in higher education: Some critical considerations and implications for disability-inclusive education policy reforms - Liasidou, Anastasia; Liasidou, Sotiroula (My University, 2023)
The article discusses recent Higher Education (HE) initiatives to introduce the Sunflower Scheme, which enables students with hidden disabilities to ‘discreetly’ indicate the existence of a disability to access support. A significant problem related to persons with hidden disabilities lies in their frequent reluctance to disclose their disabilities because of discriminatory attitudes that arise not only due to the dominance of arbitrary fabrications of ‘normalcy’ – aligned with elitist and human capital HE discourses – but also due to the lack of recognition of the existence of hidden disabilities. Even though the Scheme has been touted as a method that recognises hidden disabilities in HE, it, nevertheless, reinforces discourses of ‘misrecognition’ that create power inequities and project subordinated identities. The article argues that introducing the Scheme in HE constitutes another manifestation of disability-related initiatives that reinforce individual pathology and paternalistic discourses of dependency. The article contributes to a policy dialogue on the need to introduce alternative forms of provision to foster disability-inclusive practices in HE and makes a case to empirically capture the ‘lived experience’ of the Scheme in the context of Disability Equality policies in HE.
Keywords: (Hidden)disabilities; Sunflower scheme; Power inequities; Inclusive education; Higher education